Effect of Porosity of Alumina and Zirconia Ceramics toward Pre-Osteoblast Response - Hadjicharalambous, Chrystalleni; Prymak, Oleg; Loza, Kateryna; Buyakov, Ales; Kulkov, Sergei; Chatzinikolaidou, Maria (Frontiers in Bioengineering and Biotechnology, 2015)
It is acknowledged that cellular responses are highly affected by biomaterial porosity. The investigation of this effect is important for the development of implanted biomaterials that integrate with bone tissue. Zirconia and alumina ceramics exhibit outstanding mechanical properties and are among the most popular implant materials used in orthopedics, but few data exist regarding the effect of porosity on cellular responses to these materials. The present study investigates the effect of porosity on the attachment and proliferation of pre-osteoblastic cells on zirconia and alumina. For each composition, ceramics of three different porosities are fabricated by sintering, and characterized using scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray powder diffraction. Cell proliferation is quantified, and microscopy is employed to qualitatively support the proliferation results and evaluate cell morphology. Cell adhesion and metabolic activity are found comparable among low porosity zirconia and alumina. In contrast, higher porosity favors better cell spreading on zirconia and improves growth, but does not significantly affect cell response on alumina. Between the highest porosity materials, cell response on zirconia is found superior to alumina. Results show that an average pore size of ~150 µm and ~50% porosity can be considered beneficial to cellular growth on zirconia ceramics.